Analisis Transparansi dan Akuntabilitas Pemerintah Desa terhadap Pengelolaan Dana Desa (DD) di Desa Panaguan Kecamatan Larangan Kabupaten Pamekasan - Citra Larashati Surya; Alfi Hasaniyah (Al-Amien Prenduan for Islamic Institute, 2022)
This research aims to analyze the application of the principle of transparency dan the principle of accountability in the stages of planning, implemantation, reporting an accountability for the management of village funds in Panaguan Village Larangan District Pamekasan Regency. This type of research uses qualitative research methods that use a descriptive approach. The source of data used in this research is the primary data source obtained directly from the object of research conducted by interviewing the object which in this case is the Panaguan village government, as well secondary data source obtained from library research, documentation, and legislation. The data collection technique used in this research is by means of interviews an documentation. The results of this research indicate that the Panaguan Village Government has applied the principles of transparency an accountability to the management of village funds in Panaguan village. The Panaguan Village Government is responsible to yhe community, the BPD, and the Regent to carry out the activity plans that have been prepared in the village meeting. Open access to information on the planned activity that has been prepared is conveyed to the public by placing banners or billboards containing information about the Panaguan APBDes. At the implementation stage, the activity implementation team is responsible for the implementation of the work program. The community is also involved in the implementation of the work program. And information about the details of the activities is given in the form of project information board. In the reporting and accountability stage, the village government is responsible for providing periodic reports to the BPD and the Regent. The Panaguan village treasurer has also used the Siskeudes application in making village reports. Information disclosure for the community is provided through the installation of information on the use of village funds in strategic places.